Pengaruh Budaya Organisasi dan Motivasi Kerja terhadap Kinerja Karyawan PT. Kereta Api Indonesia (Persero) DAOP VI Yogyakarta (Studi Kasus Karyawan Stasiun Jenar, Wojo, Wates, Sentolo; Resort Jj 6.1 Jenar, 6.2 Wojo, 6.3 Wates; Resort Sintelis 6.1 Wates) - Suhartini, Yati; Prasetyanta, Nindya Putra (Akmenika, 2013)
This research examines the effects of organization culture and work motivation to employee performance in PT. Kereta Api Indonesia (PERSERO) DAOP VI Yog-yakarta.The population of this research are 95 employees who are also used as the samples of the research. Data were collected by using a questionnaire and analyzed by using multiple regressions which is also applied for testing the 4 hypotheses. All of the process analyses are assisted by SPSS programs.The results of analyses show that : (1) there are positive effecs between organization culture and working motivation to employee performance; F-test amounting to 39,662 and the significance level pointing at 0,000 (<0,05), (2) there is a positive effect on organization culture to employee performance; (3) there is a positive correlation between working motivation and employee performance; T-test and the significant level of each variable of organization culture and working motivation are 2,494 and 0,016(<0,05); 4,998 and 0,000(<0,05); respectively.(4) where as the most influencing independent variable is working motivation. Finally, the result of adjusted R square is counted to 0,617.